2015
DOI: 10.1016/j.chb.2015.05.043
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of speaking up behavior during conflict with real and virtual humans

Abstract: 2016-11-02T18:49:00

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 35 publications
1
25
0
Order By: Relevance
“…Prior research has explored whether the agency of an antagonist (e.g., the surgeon who must be spoken up to) impacts the rate and manner in which participants speak up (Robb et al, 2015b). This research found that the antagonist's agency had no significant effect (p = 0.869).…”
Section: Discussionmentioning
confidence: 48%
See 3 more Smart Citations
“…Prior research has explored whether the agency of an antagonist (e.g., the surgeon who must be spoken up to) impacts the rate and manner in which participants speak up (Robb et al, 2015b). This research found that the antagonist's agency had no significant effect (p = 0.869).…”
Section: Discussionmentioning
confidence: 48%
“…Examples include virtual teammates for procedural skills training (Rickel and Lewis Johnson, 1999), military negotiation training (Hill et al, 2003), operations training (Remolina et al, 2005), unmanned Ariel vehicle operation (Ball et al, 2010), postoperative care training (Chuah et al, 2013), and patient safety negotiations (Robb et al, 2016). Similar to team training studies involving teams comprised of humans only, research involving virtual teammates has also demonstrated positive effects on skill development (Kroetz, 1999), team performance (Demir and Cooke, 2014), and issues involving patient safety (Robb et al, 2015b).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The last studies in this group examined the methods of speaking up and their effectiveness. 35,42,43 A pilot program which taught staff at a Congolese hospital to implement the surgical safety checklist was examined. Participants reported that training had a positive effect on teamwork, organisation, and safe anaesthesia practices.…”
Section: Do Qualitatively Identified Barriers Have a Significant Effementioning
confidence: 99%